FUNCTIONAL FOUNDATIONS OF AXIOLOGICAL APPROACH TECHNOLOGIES IN READING EDUCATION - Mambetaminov, Nurlybay Mambetsapayevich (SCIENCE and SOCIETY, 2026)
This article provides a comprehensive analysis of the functional foundations of axiological approach technologies in reading literacy education. The relevance of the research is explained by the need to form in students competencies not only for reading and understanding the text, but also for understanding its content based on value criteria, assessment, and expression of personal attitude in the modern educational process. The article examines the theoretical and methodological principles of the axiological approach, the cognitive, communicative, and axiological components of reading literacy in interconnection. The didactic possibilities of value-oriented pedagogical technologies, the mechanisms for organizing reflection, interpretation, and assessment activities in the process of working with text, are also highlighted.